(untitled) (Global Journal of Human-Social Science, 2016)
This paper presents a discussion about how current changes in welfare regime in Cuban current context limit poor families capabilities of resilience and opportunities for overcoming poverty From the analysis of contextual changes in welfare regime in the country it is analyzed the role and relationships between State social policies market based transactions and families informal support networks in families coping strategies Based on qualitative methodology the study evidenced a contradiction between the formal tendency to reinforce commodification and familiarization of welfare and the strong dependency poor families have from State support and traditional de-commodificated welfare regime in Cuba This contradiction supposes an essential challenge to social equity in the current process of Actualization of Cuban Development Model